Factors Influencing Choice of Specialty amongst Nigerian Ophthalmologists - Oluwole, Omolase Charles (Pakistan Journal of Ophthalmology, 2018)
Purpose: To determine the factors that influenced the choice of specialty amongst Nigerian Ophthalmologists. Material and Methods: This study was conducted during the annual congress and scientific conference of the Ophthalmological society of Nigeria which took place at the Obafemi Awolowo University, Ile-Ife, Osun State, Nigeria between 14th and 18th September, 2008 The respondents were interviewed with the aid of structured questionnaire by the author and three assistants. The data obtained with the study instrument (questionnaire) included the time the respondents opted for Ophthalmology and the factors that influenced their choice. The data obtained was analyzed with SPSS 12.0.1 statistical soft ware. Results: There were eighty respondents comprising of 33 (41.25%) Consulants, 2 (2.5%) Diplomats and 45 (56.25%) resident doctors. About a third of the respondents, 26 (32.5%) opted for Ophthalmology after their one year youth service. The factors that influenced their choice of specialty were mainly interest in the specialty, 68 (85%), opportunity to combine medicine and surgery, 27 (33.8%) as well as life style, 34 (42.5%). Conclusion: Interest in the specialty was the leading factor that influenced choice of Ophthalmology.